An investigation on the need for business advisors who can respond to the changing needs of small business enterprises faced with a dynamic operating environment. (20th December 2021) - Chikweche, Tendai; Bressan, Alessandro
Abstract: The purpose of this paper is to demonstrate the need for Business Advisors (BAs) who are not only capable of responding to small business enterprises' (SBEs) current constraints but also capable of responding to their evolving needs due to the changing context and their growth. This dynamic environment is characterised by issues such as changing legislation, technology disruption and ethnic diversity. This research is an exploratory study that adopts a multiple case method approach. Data was collected from SBEs and BAs using interviews. Propositions from the study indicate that the new environment has created a greater demand for diverse services that address emerging new needs for SBEs. This includes demand for advisory services in new niche business areas. Trust, integrity, knowledge and advisory experience emerged as a portfolio of principles and skills that SBEs look for in a BA, in order for them to address their evolving needs. Availability of new integrated technology platforms is changing SBEs' preferences of contact methods and BAs' own usage of these platforms to engage SBEs. Practical and policy implications include need for regular review of relevant legislation; continuous professional development, establishment of sector specialists and an industry Advisory Council that will monitor practices and provide continuous professional training for BAs.